Glyph Visualization - A fail-safe design scheme based on quasi-Hamming distances - Legg, P; Maguire, E; Walton, S; Chen, M (Institute of Electrical and Electronics Engineers, 2016)
In many applications of spatial or temporal visualization, glyphs provide an effective means for encoding multivariate data. However, because glyphs are typically small, they are vulnerable to various perceptual errors. In information theory, Hamming distance underpins the study of codes that support error detection and correction by the receiver without the need for corroboration from the sender. In this work, we propose the novel concept of quasi-Hamming distance for glyph design. We examine the feasibility of estimating quasi-Hamming distances between glyph pairs, and the minimal Hamming distance for a glyph set. This measurement enables glyph designers to determine differentiability between glyphs, facilitating design optimization by maximizing distances between glyphs under various design constraints. We demonstrate this concept with a case study of visualizing file system events for multiple users. Our study shows that quasi-Hamming distances facilitate separability in glyph design and help to reduce the vulnerability of glyph-based visualization.